2007
DOI: 10.1016/j.coi.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk at the initial encounter: interplay between host defense and ameba survival strategies

Abstract: The host-parasite relationship is based on a series of interplays between host defense mechanisms and parasite survival strategies. Progress has been made in understanding the role of host immune response in amebiasis. While host cells elaborate diverse mechanisms for pathogen expulsion, amebae have also developed complex strategies to modulate host immune response and facilitate their own survival. This paper will give an overview of current research on the mutual interactions between host and Entamoeba histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 79 publications
2
37
0
Order By: Relevance
“…In contrast, serum IgA has not been correlated with infection. Therefore, it is suggested that the systemic anti-Hgl antibody response may not offer direct protection from amebiasis (19). The details of the humoral immune response to Igl are unknown, but we have observed that serum antibodies to Igl are detected not only in symptomatic patients but also in asymptomatic E. histolytica cyst passers (46).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, serum IgA has not been correlated with infection. Therefore, it is suggested that the systemic anti-Hgl antibody response may not offer direct protection from amebiasis (19). The details of the humoral immune response to Igl are unknown, but we have observed that serum antibodies to Igl are detected not only in symptomatic patients but also in asymptomatic E. histolytica cyst passers (46).…”
Section: Discussionmentioning
confidence: 79%
“…However, we suspect that the in vivo effect of Fab fragments to E. histolytica trophozoites will be restricted because of the lack of an Fc region. Since the MAbs described in this paper are complete immunoglobulins, the effects of human MAbs on E. histolytica trophozoites in vivo may be induced with complement activation through the classical pathway (19). Indeed, it is well-known that IgM, in particular, is a mediator of complement activation.…”
Section: Discussionmentioning
confidence: 97%
“…The cause of this phenomenon is likely complex and multifactorial; however, it is possible that the differences in regulation over time are due to the kinetics of E. histolytica infection. It has been previously suggested that E. histolytica establishes infection sequentially, beginning with attachment to and degradation of the mucus layer, followed by invasion and destruction of the epithelial layer, and finally invasion into the lamina propria and damage of the enteric nervous system (67)(68)(69). Thus, it is likely that at early time points during infection (i.e., at 12 h) transcriptional changes are due to superficial invasion of the mucosa, while later responses represent deeper invasion and more tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other factors such as oxygen reduction ability, complement resistant, ROS and NOS scavenger capacity and immune evasion of the parasites also contribute to the parasites survival. Once the parasites are able to adapt to the environment in the liver, inflammation will be stimulated and followed by extensive tissue destruction [8,15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Contents lists available at ScienceDirect followed by extensive necrosis with fused granulomas [7][8][9] .…”
Section: Pas Ihc Trophozoitementioning
confidence: 99%